Upaya Penggunaan Media Visual Tiga Dimensi untuk Meningkatkan Minat Belajar Siswa Mata Pelajaran Kewarganegaraan di SMK Nurul Iman Bantul - Noviati, Nunik; Budiutomo, Tri Wahyu (Academy of Social Science and Global Citizenship Journal, 2021)
The problem of education in Indonesia is very complex, especially in terms of teaching aids. In this era of globalization, there are many learning methods used by teachers or teaching staff, one of which is visual media. With this visual media, the main goal is to be able to attract students' interest in learning Pendication Kewarganegaraan is much more efficient and effective, because the visual media that researchers expose is a three-dimensional visual media like a puzzle called the Garuda Lima Pilar Medal. This medium is created in such a way, which is interesting and constructed so that what the student learns can be easily understood, understood, remembered, and then its meaning can be applied in daily life.